Guía didáctica de Contabilidad General para la enseñanza de los estudiantes del Primer año de Bachillerato de la Unidad Educativa Fiscomisional San José de Calasanz, del cantón Saraguro, Período 2021. - Guazha Morocho, Rosa Angélica (2023)
The Curricular Integration Work called "Didactic Guide of General Accounting for the teaching of students in the first year of High School of the San José de Calasanz Fiscomisional Educational Unit, Saraguro canton, Period 2021", was carried out prior requirement to obtain the degree of Bachelor in Accounting and Auditing, developed according to the Academic Regulations of the National University of Loja, with the aim of providing the educational institution with an instrument for the teaching-learning process of the specialty of Accounting, and thus, strengthen the level of knowledge of young students. To meet the objectives set out in the Curricular Integration Work, first, a research instrument was applied to the legal representative of the Educational Unit, teachers and students of the First Year of Technical High School, Professional Figure Accounting for the academic period 2021, where the importance of the implementation of a didactic guide of General Accounting as an easy-to-use tool in the learning process of students was established. For the execution of the second objective on the determination of the required and necessary information for the foundation of the theoretical and practical references for the development of the didactic document, we proceeded in the first instance with the obtaining of the Accounting Curricular Planning of the academic period 2021, provided by the teacher of the Technical Area - FIP Accounting; which served as a reference framework for the establishment of the theoretical and practical contents that the student must take in the first year; where the accounting information was compiled and classified in an orderly manner according to the requirements and needs of the students. In the fulfillment of the third objective, we focused on the implementation of the General Accounting Didactic Guide, which gathers information and basic aspects of accounting science in a creative, coherent and understandable way, with the purpose of promoting motivation and development of logical, reflective and active thinking in the students. Finally, the following conclusion was drawn: the General Accounting Teaching Guide is a valid tool to strengthen the teaching-learning process of the Accounting specialty, by providing accounting information to students for their technical training, and thus, raising their level of knowledge. It is also important to mention that this work will serve as a source of support and information for future students entering the Technical Area - FIP Accounting.